Towards a Malawian theology of laity - Glissmann, Volker (Luviri Press, 2021)
The aim of this book is to bring together different contributors to address biblically and theologically the role of the laity within the context of the Malawian church. Contributions come from active church leaders within the Malawian church, theological educators reflecting within institutions in Malawi as well as Malawian theologians who serve outside of Malawi. Also, contributions from practitioners who are actively involved in grassroots and church ministry. Finally, the voices of Malawian lay Christians were also collected through interviews. [Abstract ASC Leiden].